Long-term performance of a hybrid indirect evaporative cooling-mechanical vapor compression cycle: A case study in Saudi Arabia - Chen, Qian; M, Kum Ja; Burhan, Muhammad; Shahzad, Muhammad Wakil; Ybyraiymkul, Doskhan; Oh, Seungjin; Cui, Xin; Ng, Kim Choon (Frontiers in Built Environment, 2022)
In Saudi Arabia, air conditioning is the main consumer of electricity, and increasing its energy efficiency is of great importance for energy conservation and carbon footprint reduction. This study presents the evaluation of a hybrid indirect evaporative cooling-mechanical vapor compression (IEC-MVC) cycle for cooling applications in Saudi Arabia. Most cities in this country are characterized by a high sensible cooling demand, and a few cities near the coasts of the Red sea and the Persian Gulf also need dehumidification. By employing the hybrid system, IEC can undertake about 60% of the cooling load in the summer of arid cities, and energy consumption can be reduced by up to 50%. The contribution of IEC and energy saving are less significant in humid cities because the latent loads have to be handled by MVC. Over the whole year, IEC contributes 50% of the total cooling capacity and reduces energy consumption by 40% in dry cities, while the saving is lower at 15%–25% in humid cities like Mecca and Jeddah. The average water consumption of the IEC is in the range of 4–12 L/hr. The water consumption can be replenished by the condensate collected from the MVC evaporator if the ambient humidity is high. Based on the annual performance, the cost of the IEC-MVC process is calculated, and it is 15%–35% lower than the standalone MVC. The results demonstrate the great potential of the hybrid IEC-MVC cycle in Saudi Arabia.